Projected Land Use Change Based on Protected Scenarios in Malang City - Andri Kurniawan; Hanif Ananta Damar Muzaqqi (Universitas Negeri Medan, 2026)
Regional spatial planning often requires studies of projected land-use changes. However, these land-use change projection studies often neglect the protection function aspect in their modeling scenarios. Modeling using protection function scenarios is expected to make a significant theoretical and practical contribution to regional spatial planning and geospatial analysis. The research aims to develop a model for projecting land use change based on protected scenarios to support sustainable development in Malang City. Projection of land-use change based on scenarios is carried out quantitatively and involves spatial modeling. Spatial modeling was carried out using Cellular Automata (CA), which is integrated with Markov Chain (MC) and Artificial Neural Network (ANN). Hybrid modeling of Cellular Automata (CA) – Markov Chain (MC) – Artificial Neural Network (ANN) is expected to offer more attractive advantages compared to single modeling techniques. The model was developed by paying attention to the driving factors and constraint variables as scenario variables in the form of maintained protected areas. This research produced a projected model of land use change in 2029 based on a protected scenario in Malang City. The projection results indicate potential land change for sizable settlements in Malang City, especially in the eastern and western parts around the center of activities and the Malang-Pandaan toll road. The potential development of these settlements needs to be anticipated and directed so that they do not cause various spatial conflicts in the future and do not trigger environmental degradation. With scenario-based projections, several protected areas such as city parks, green belts, city forests, and river banks can be relatively maintained in 2029 according to the spatial pattern plan in the Malang City spatial plan.